THE CATION EXCHANGE CAPACITY OF THE GREEK ZEOLITIC ROCKS - Filippidis, A.; Kantiranis, N.; Stamatakis, M.; Drakoulis, A.; Tzamos, E. (Bulletin of the Geological Society of Greece, 2007)
Forty two zeolitic rock samples, from the Prefectures ofEvros, Rhodope, Samos and Cyclades, have been investigated for their cation exchange capacity (CEC, in meq/100g) and the mineralogical composition (wt.%), using the Ammonium Acetate Saturation method and Powder X-ray Diffraction method, respectively. HEU-type zeolite (heulandite-clinoptilolite) was found in Ρ etrota area (43-89 wt.%, CEC 101- 217), Samos island (34-91 wt.%, CEC 93-217), Pentalofos area (68-74 wt.%, CEC 124-202), Metaxades area (47-64 wt.%, CEC 119-140) and Thira island (33 wt.%, CEC 118). Mordenite was found in Samos island (64 wt.%, CEC 150), Polyegos island (61 wt.%, CEC 136), Thira island (56 wt.%, CEC 130), Milos island (45 wt.%, CEC 97), Kimolos island (30 wt.%, CEC 96) and Feres area (5 wt.%, CEC 22). Analcime was found in Samos island (27-71 wt.%, CEC 104-285) and Darmeni area (16 wt.%, CEC 62). Chabazite was found in Samos island (66 wt.%, CEC 243). HEU-type zeolite+mordenite were found in Feres area (45-74 wt.%, CEC 132-209), Samos island (81 wt.%, CEC 184), Thira island (72 wt.%, CEC 177), Polyegos island (66 wt.%, CEC 153) and Skaloma area (51-60 wt.%, CEC 126-143). HEUtype zeolite+phillipsite were found in Samos island (47 wt.%, CEC 170) and HEUtype zeolite+analcime were found in Samos island (55 wt.%, CEC 129). The CEC of the zeolitic rocks show positive correlations with the type of zeolite and the microporous minerals (zeolites+micas+clay minerals) content, mainly affected by the zeolites and to lesser extent by micas and clay minerals.